Antioxidant attributes of tea in North Bengal, India: Relation with its principal constituents and properties of soil - Misra, Tarun Kumar; Saha, Aniruddha; Nanda, Ashis Kumar; Bagchi, Subhrajyoti; Mandal, Palash (Journal of Plantation Crops, 2022)
This study was performed in 18 tea gardens in North Bengal, India, from 2012 to 2017. The data were pooled to investigate the relationship with soil physico-chemical properties, phyto-constituents, antioxidant attributes and age of the tea bushes and principal component analysis (PCA). PCA and dendro-hit maps were also performed with each region. The 28 principal components were chosen based on their eigen values, explaining the total data variance for tea in Dooars, Terai and Darjeeling hill. In almost all cases, composite soil physico-chemical attributes were heavily loaded on the second principal component and clustered, as visual evidenced by the dendro-hit map. Different attributes were significantly correlated each other in case of Terai i.e. (value of “r’’ at P<0.01 level) clay fraction (0.778), electrical conductivity (0.618), N (0.777), S (0.748), P (0.514 ppm), flavour index (0.918), total polyphenol (0.687) DPPH (0.794), nitric oxide (0.913), anti-lipid peroxidation (0.717) and metal chelating (0.665). In Dooars region, attributes were significantly correlated with silt (0.718), pH (0.875), P (0.615 ), chloride (0.858), TP (0.776), flavonol (0.923), quinone (0.666), tannins (0.865), DPPH (0.536), superoxide (0.576), ABTS (0.520) and MC (0.777) and in the case of Darjeeling hills, attributes were highly correlated with clay (0.812), sand (0.818), silt fraction (0.974), K (0.932), S (0.999), MC of soil (0.671), TP (0.853), tannins (0.912), DPPH (0.624), ABTS (0.661) and MC (0.633) repectively.